2019
DOI: 10.1042/bcj20190224
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the mechanism of action of HtrA4: a serine protease implicated in the cell death pathway

Abstract: High-temperature requirement protease A4 (HtrA4) is a secretary serine protease whose expression is up-regulated in pre-eclampsia (PE) and hence is a possible biomarker of PE. It has also been altered in cancers such as glioblastoma, breast carcinoma, and prostate cancer making it an emerging therapeutic target. Among the human HtrAs, HtrA4 is the least characterized protease pertaining to both structure and its functions. Although the members of human HtrA family share a significant structural and functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In the bacterial HtrAs such as DegS, DegP and DegQ, it is well documented that their active site pockets get allosterically stabilized or activated by substrate binding at the distal regulatory PDZ domain [59]. For the human HtrAs, an allosteric mode of activation is well established in the literature for all human HtrAs (-1,-2 and -4) except HtrA3 [12,13]. We recently demonstrated that an allosteric mode of regulation exists for HtrA3 through a novel non-canonical pocket spanning residues both in the SPD and PDZ domains [18].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In the bacterial HtrAs such as DegS, DegP and DegQ, it is well documented that their active site pockets get allosterically stabilized or activated by substrate binding at the distal regulatory PDZ domain [59]. For the human HtrAs, an allosteric mode of activation is well established in the literature for all human HtrAs (-1,-2 and -4) except HtrA3 [12,13]. We recently demonstrated that an allosteric mode of regulation exists for HtrA3 through a novel non-canonical pocket spanning residues both in the SPD and PDZ domains [18].…”
Section: Discussionmentioning
confidence: 98%
“…Human HtrAs are primarily trimeric [13,14] while their prokaryotic counterparts are capable of forming higher-order oligomers [3]. HtrA3 crystal structure represents a trimeric ensemble of three molecules of the monomeric protein where three phenylalanine residues (F140, F142 and F255) from each monomeric chain 'lock' together to stabilize the trimer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations